2004
DOI: 10.1111/j.1365-2893.2004.00535.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus infection in Egyptian children: single centre experience

Abstract: The outcome of hepatitis C virus (HCV) infection acquired in childhood is uncertain because of the diversity of the epidemiological and clinical features of infection and disease. The aim of this study was to determine the outcome of HCV infection in 105 Egyptian children who tested positive for HCV antibody (anti-HCV). The data of 105 anti-HCV-positive children presenting to the Pediatric Hepatology Unit, Cairo University Children's Hospital, between 1995 and 2002, were retrospectively analysed for risk facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 32 publications
2
19
1
Order By: Relevance
“…This association may be due to intervention of multiple risk factors as children with chronic disease are more vulnerable to frequent hospitalization which increases possibility of contact with HCV infected persons, also those children are more exposed to injection and invasive procedures. This association was not reported in the previous studies was done in Egypt [3,7,12,15]. However, Barakat et al [3] excluded children with a history of chronic disease.…”
Section: Discussioncontrasting
confidence: 41%
“…This association may be due to intervention of multiple risk factors as children with chronic disease are more vulnerable to frequent hospitalization which increases possibility of contact with HCV infected persons, also those children are more exposed to injection and invasive procedures. This association was not reported in the previous studies was done in Egypt [3,7,12,15]. However, Barakat et al [3] excluded children with a history of chronic disease.…”
Section: Discussioncontrasting
confidence: 41%
“…A recent study of intrafamilial transmission showed that the incidence of offsprings to acquire HCV from anti-HCV-positive parents is slightly higher (incidence rate of 8.7/1000 per year) in the positive mother than in the anti-HCV positive father (6.6/1000) [12] . According to a study by El-Raziky et al [13] HCV infection is not always benign in the Egyptian children as ALT levels are elevated in half of the subjects and www.wjgnet.com histological abnormalities are detectable in three quarters of HCV-RNA positive cases. It is not clear whether identification of HCV early in childhood can alter the course of the disease due to the limitations of current antiviral therapies.…”
Section: Introductionmentioning
confidence: 99%
“…The outcome of HCV infection acquired in childhood is uncertain as a result of the variation of clinical course of infection and disease in children [11] . HCV infection is not always benign in the childhood period, a recent study in Egypt showed that, ALT levels were elevated in half of the subjects and histological abnormalities were detected in three quarters of HCV-RNA positive cases [12] . Because of the major long-term complications of chronic HCV, and www.wjgnet.com the development of cirrhosis and end-stage liver disease, the degree of fibrosis on liver biopsy would seem to be an appropriate surrogate marker [13] .…”
Section: Introductionmentioning
confidence: 99%